Modification of Oil Palm Empty Fruit Bunch Fibers by Nanoparticle Impregnation and Alkali Treatment - Chowdhury, M. N. K.; Beg, M. D. H.; Khan, Maksudur R.; M. F., Fina (Springer Netherlands, 2013)
Oil palm empty fruit bunch (EFB) fibers were impregnated by copper nanoparticles (CuNPs) through the cationization process as well as treated by alkali solutions. Mechanical properties of different single fibers were measured and analysed by the Weibull statistical distribution. The weak link scaling of Weibull analysis has provided valuable information to scale the strength of one EFB fiber to predict the strength of other one. The impregnation and interfacial interaction of CuNPs with fibers has been analysed by Fourier transformed infrared spectroscopy, X-ray diffraction study, field emission scanning electron microscopy, energy dispersive X-ray study and thermogravimetric analysis. A significant increase in mechanical property of modified fibers with respect to the control ones has been observed. The crystallinity and thermal stability of the treated fibers were also found to be changed. These findings strongly suggest that CuNPs can be used as an effective reinforcing agent in natural fibers to improve their mechanical property and durability.